Ninety-Day Complications Following Total Hip Arthroplasty with Computer Navigation versus Conventional Techniques - Peterson, Blaire; Kotzur, Travis; Singh, Aaron; Parker, John; Buttacavoli, Frank; Moore, Chance (The Surgery Journal, 2025)
Computer navigation is associated with improved limb alignment and implant position in total joint arthroplasty. While it is commonly used in total knee arthroplasty, adoption in the setting of total hip arthroplasty (THA) has been slower. Further, the literature is equivocal on whether computer navigation improves outcomes. The aim of this study was to assess the impact of computer navigation on outcomes in the setting of THA.This was a retrospective cohort study. The National Readmissions Database, from 2016 to 2020, was queried via International Classification of Diseases, Tenth Revision (ICD-10) codes for all patients undergoing THA. To compare outcomes between conventional and computer-navigated THA, propensity score matching was used. In the matched cohort, logistic regression was applied to evaluate postoperative complications, while negative binomial regression was used to analyze readmissions, reoperations, and discharge disposition. Gamma regression with a log-link function was utilized to assess hospital charges and length of stay.We identified a total of 1,191,362 patients undergoing primary THA. After successful matching, there were 12,918 patients in each cohort. Computer navigation was associated with increased blood transfusions (odds ratio [OR] 2.72; p < 0.001). There were no significant differences in all-cause medical complications (p = 0.123). Computer-navigated procedures were associated with significantly reduced 90-day readmission (OR 0.85; p = 0.028); however, total charges were greater (OR 1.31; p = 0.002).We found that computer-navigated THA was significantly more expensive but had reduced short-term readmission following surgery. While there were increased odds of blood transfusion, computer navigation may still be safe and beneficial in appropriately selected patients.
Keywords: computer navigation; total hip arthroplasty; short-term outcomes